Existential Conception of Freedom - Buračas, Giedrius (Problemos, 1988)
An attempt is made to reconstruct the evolution of the conception of freedom in the existential philosophy. The reconstruction is based upon an axiological approach, and the views of the most prominent existential philosophers, including, Kierkegaard, Husserl and Heidegger are considered. First, the comparative analysis of the views is done, and then the interpretation in the terms of the historical materialism is given.